Pemberian Motivasi Untuk Meningkatkan Kinerja Karyawan PT. ‎Langkat Nusantara Kepong - Aulia, Muhammad Reza; Siregar, Mawaddah Putri Arisma (IKHLAS: Jurnal Pengabdian Dosen dan Mahasiswa, 2023)
The lack of motivation that employees have in carrying out work responsibilities often results in poor performance for the company. The service aims to increase the motivation of PT. Langkat Nusantara Kepong (LNK) so that employees who have high motivation are formed, so that there is an increase in performance. The method of implementing this service is carried out in several activities, namely a survey to determine the location of the service, preparing materials and conducting training. Then 4 gardens were chosen as the location of the dedication, namely: Basilam, Bekiun, Gohor Lama and Padang Brahrang. The team implementing the community service activities is a lecturer at the Faculty of Agriculture, University of Teuku Umar. The dedication team provides material that fosters motivation such as explanations on how to become employees with integrity, creative and innovative professionals. Furthermore, the stage of sharing experiences or question and answer discussion is carried out. The results of this community service can be concluded that employees need motivation. It is hoped that the company pays attention to the form of motivation given to employees, for example giving rewards, if employees are motivated then performance will improve. High work motivation will create employees who are swift in carrying out tasks.